Inventario de Regatas como Atractivo Turístico de la Provincia de Los Ríos - Martínez Castillo, Mylena Cristina (2022)
This study seeks to answer the question: What is the inventory of regattas in the province of Los Ríos? Where its main objective is to define that inventory of regattas as a tourist attraction in the province, through documentary and exploratory research, using the qualitative-inductive method through observation and interview techniques, for which the file was adapted for the survey. and hierarchy of tourist attractions of the MINTUR. As a result of this research work, it was possible to determine that there are 12 places where regattas are held in the province, located in 6 cantons, with 5 different types. Through this research, it is sought that the authorities use the information collected to establish a calendar and inform the population about the places where the regattas are held to improve tourism planning and, in turn, catalyze the economy of the province through the tourism.